EFFECTIVENESS OF PUBLIC INSTITUTIONS IN ADDRESSING ILLEGAL ACQUISITION OF STATE LAND IN ZAMBIA: Case of Ministry of Lands and Kitwe Municipality - Anthony Mushinge (African Journal on Land Policy and Geospatial Sciences, 2022)
Like in a number of African countries, the issue of illegal acquisition of state land is evident in Zambia. There are public land institutions (that is, Ministry of Lands and Natural Resources and Local Authorities) mandated to deal with illegal acquisition of state land in the country. Despite the existence of the two public institutions, evidence shows a high frequency of illegal acquisition of state land in the country. Thus the key question for this paper was: how effective are these public institutions in dealing with cases of illegal occupation of land in Zambian cities? This paper aims at investigating the challenges faced by public land institutions in dealing with the illegal acquisition of state land and establishing the consequences of illegal acquisition of state land. This study has revealed that the two public land institutions face various challenges in addressing illegal acquisition of state. Challenges among others included limited provision of information on land acquisition procedure to the public, failure to address illegal allocation of land by some Councillors and council employees as well as some political cadres, and poor land record keeping. Moreover, illegal acquisition of state land had consequences which included demolition of properties, violence, disruption in land use planning, and loss of government revenue. In view of the foregoing, illegal acquisition can be addressed through: sufficient provision of information on land acquisition procedure to the public; eradicating illegal allocation of land by some Councillors and council employees as well as some political cadres; improving land record keeping by digitisation of land record keeping by local authorities and ultimately strong political will to deal with this vice.